Analysis of multi-phase coupled seepage and stability in anisotropic slopes under rainfall condition - Wu, L. Z.; Zhang, L. M.; Zhou, Y.; Li, B. E. (Environmental earth sciences, 2017)
The seepage, deformation and stability in unsaturated soil slopes under rainfall infiltration are important issues in geotechnical engineering. Based on multi-field coupling theory, a finite element code, COMSOL, is employed to solve the coupled partial differential equations for soil slopes under rainfall infiltration. The coefficient of permeability is a variable in the three-phase coupled model. The water seepage, air migration, deformation and stability in a soil slope due to precipitation are studied. The effect of the wetting front caused by the migration of pore-air and the deformation of soil are explored, and the impact of soil anisotropy is analysed. The results indicate that the effect of anisotropy on the pore-water pressure is related to the depth and position of the unsaturated soil slope. The factor of safety of the partially saturated slope is relatively high when the lateral coefficient of permeability of the slope is greater than the coefficient of permeability in the vertical direction. The factor of safety is a function of the degree of anisotropy.